(untitled) (International journal of artificial intelligence, 2025)
This paper analyzes the theoretical foundations and practical applications of positional and metric problems. It focuses on improving the content of methodological recommendations through a comparative study of existing approaches and the development of more efficient algorithms. Practical experiments demonstrate the effectiveness of the proposed improvements in real-world scenarios.